Assessment of Export Efficiency Equations in the Southern Ocean Applied to Satellite‐Based Net Primary Production. Issue 4 (26th April 2018) - Arteaga, Lionel; Haëntjens, Nils; Boss, Emmanuel; Johnson, Kenneth S.; Sarmiento, Jorge L.
Abstract: Carbon export efficiency (e‐ratio) is defined as the fraction of organic carbon fixed through net primary production (NPP) that is exported out of the surface productive layer of the ocean. Recent observations for the Southern Ocean suggest a negative e‐ratio versus NPP relationship, and a reduced dependency of export efficiency on temperature, different than in the global domain. In this study, we complement information from a passive satellite sensor with novel space‐based lidar observations of ocean particulate backscattering to infer NPP over the entire annual cycle, and estimate Southern Ocean export rates from five different empirical models of export efficiency. Inferred Southern Ocean NPP falls within the range of previous studies, with a mean estimate of 15.8 (± 3.9) Pg C yr −1 for the region south of 30 ° S during the 2005–2016 period. We find that an export efficiency model that accounts for silica(Si)‐ballasting, which is constrained by observations with a negative e‐ratio versus NPP relationship, shows the best agreement with in situ‐based estimates of annual net community production (annual export of 2.7 ± 0.6 Pg C yr −1 south of 30 ° S). By contrast, models based on the analysis of global observations with a positive e‐ratio versus NPP relationship predict annually integrated export rates that are ∼ 33% higher than the Si‐dependent model. Our results suggest that accounting for Si‐induced ballasting is important for the estimation of carbon export in the Southern Ocean. Plain Language Summary: The amount of organic carbon that is exported from the surface to the deep ocean exerts an important control on atmospheric carbon dioxide and the transfer of organic material across trophic levels. In this study, we make use of novel satellite information, combined with autonomous profiling floats, to estimate the efficiency and the amount of organic carbon exported in the Southern Ocean by phytoplankton. We find that previous global formulations can overestimate the amount of carbon exported in this region, and that taking into account the oceanic surface silica concentration is necessary to accurately estimate carbon export in the Southern Ocean. Key Points: Multiple formulations of export efficiency where applied to satellite‐based data to estimate carbon export in the Southern Ocean Novel lidar and MODIS data were combined to estimate phytoplankton biomass and primary productivity throughout the full annual cycle The best export efficiency model is based on a negative productivity versus e‐ratio relationship, and accounts for Si‐induced ballasting